Virtual visualization: Preparation for the Olympic Games long-track speed skating - Sorrentino, R. M.; Levy, R.; Katz, L.; Peng, X. (International Journal of Computer Science in Sport, 2005)
Visualization is a known preparation tool for athletic competition. This study used a virtual environment of the Salt Lake City Olympic Oval as a tool to support visualization to help athletes prepare for the 2002 Winter Olympic Games. Five long-track speed skaters from the Canadian Olympic Team used the virtual environment with their sport psychology consultant to prepare for the Olympics prior to leaving for Salt Lake City. All five skaters had previously visited the competition venue and found the virtual environment to be very realistic. In addition, skaters commented that they had struggled with visualization and, consequently, they thought that having the virtual venue provided for them was very useful. After using the environment, athletes indicated that they felt less anxious about going to the Olympics. Experiencing the virtual environment allowed them to focus on their race, how they would prepare for the race, their race plan, and what they would think about while competing in the race. The results of this study promote the use of virtual environments for enhancing athlete visualization. Moreover, the study identifies four ways in which virtual environments can be used by athletes in preparation for competition, as well as part of their regular training program.